Pengaruh Motivasi, Disiplin dan Fokus terhadap Manajemen Waktu Mahasiswa Ma’had UIN Kiai Ageng Muhammad Besari Ponorogo Tahun 2025/2026 - Zainul Abror; Athok Fuadi (MA'ALIM: Jurnal Pendidikan Islam, 2026)
This study aims to analyze the influence of motivation, discipline, and focus on the time management of students residing at Ma’had UIN Kiai Ageng Muhammad Besari Ponorogo. The study employed a quantitative approach using a survey method. The population consisted of all students residing at Ma’had UIN Kiai Ageng Muhammad Besari Ponorogo, with a sample of 130 respondents selected using a saturated sampling technique. Data were collected through questionnaires that had met validity and reliability requirements. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results showed that, partially, motivation did not have a significant effect on time management, with a significance value of 0.512 (> 0.05). Discipline also did not have a significant effect on time management, with a significance value of 0.570 (> 0.05). In contrast, focus had a positive and significant effect on time management, with a significance value of 0.000 (< 0.05), and was identified as the most dominant variable. Simultaneously, motivation, discipline, and focus had a significant effect on time management, as indicated by the F-test significance value of 0.000 (< 0.05). The coefficient of determination (R²) was 0.554, indicating that these three variables explained 55.4% of the variance in students’ time management, while the remaining 44.6% was influenced by other factors not included in this study. Based on these findings, it can be concluded that focus plays the most important role in improving students’ time management. Therefore, efforts to strengthen students’ ability to maintain focus through academic and dormitory-based development programs are necessary to support more effective time management.